Market imperfections - Ramon P. DeGennaro (Federal Reserve Bank of Atlanta, 2005)
Market imperfections affect virtually every transaction in some way, generating costs that interfere with trades that rational individuals make, or would make, in the absence of the imperfection. Understanding these costs gives us insight regarding the total costs of transactions, where to place them, or whether to make them at all. Market imperfections also generate profit opportunities for entrepreneurs who can reduce or eliminate them. Institutions or individuals who can lower costs tracing to imperfections have a competitive advantage and can earn economic rents until competing firms adapt. Imperfections can and do change over time, but they collectively never go to zero. Identifying and solving the underlying business problems linked to these imperfections remain an ongoing challenge and profit opportunity.
Keywords: 330; Unvollkommener Markt